UNDERSTANDING THE ROLE OF JOB RESOURCES IN PROMOTING MENTAL HEALTH AMONG ACADEMICIANS IN MALAYSIAN PUBLIC HIGHER EDUCATION: A JDR FRAMEWORK - Abdul Kadir Othman; Siti Rosnita Sakarji; Siti Nur Zahirah Omar (International Journal of Accounting, Finance and Business, 2024)
Mental health among employees has been a crucial part of the sustainable development and accomplishment of the organization’s goal and objective globally. While most studies have focused on its influence on other populations, academicians have received little attention. Thus, this study focuses on the relationship between job resources and academicians’ mental health at public higher education institutions in Malaysia. Considering this, the purpose of this study is to develop a theoretical framework that would clarify how job resources affect academicians' mental health. This study uses the Job-Demand Resources model, which postulates a health impairment and motivational process, to explain how job resources (job autonomy, social support, feedback and recognition, and job security) influence demanding and resourceful features. Four hypotheses were formulated based on the previous considerations and the JD-R model assumptions. Higher-level management is urged to encourage leaders of all work departments to offer the resources and support needed to solve the challenges faced by their employees. It is expected that the management can benefit from these findings in addressing the challenges brought by the psychosocial job factors that have a potential impact on academicians' mental health.